MANAJEMEN LABA DAN MANAJEMEN IMPRESI DALAM LAPORAN TAHUNAN: PENELITIAN STRATEGI PENGUNGKAPAN PERUSAHAAN - Suripto, Bambang (Jurnal Akuntansi dan Keuangan Indonesia, 2013)
This study examines the impact of earnings management to impression management in Management Discussion and Analysis (MD&A). Earnings management is measured using an index that includes accrual discretional, income smoothing, and loss avoidance reporting. Impression management is measured using an index that includes the use of self-serving attribution and accounting explanation bias. Impression management data are obtained by content analysis of the MD&A sections of 594 annual report companies in the period between 2004 and 2009. Empirical test results show that earnings management, performance level, performance changes, and economic conditions negatively affects impression management. The study results are useful for regulators to formulate and enforce the Bapepam rules No. VIII.G.2 about annual report to minimize the possibility managers conducting earnings and impression management.